A figurativização histórico-social em contos de A cidade dorme de Luiz Rufatto. - Ricardo, Marcela (2020)
This research analyzes short stories from the collection A cidade dorme (2018), by Luiz Rufatto through the theoretical framework of discursive semiotics. The work consists of narratives in which the protagonist actors, invisible within the urban social scenario of contemporary Brazil, feel frustrated in relation to their own dreams and values, responsible for giving meaning to their existences. We selected two short stories to compose the corpus of this research, "As vantagens da morte" and "O dia em que encontrei meu pai”. We use elements from the generative path of meaning in order to analyze the construction of the subjectivity of the protagonist actors. their actorial, temporal and spatial projection in the enunciation and enunciate level, the thematic-figurative organization of the texts as well as the interdiscursive dialogue established by the enunciator with the socio-historical and ideological context. We have verifiued that the veridiction contract proposed by the enunciator to the enunciatee-reader allows his adhesion to the texts, through the ironic criticism woven by the first in relation to the theme of social and political oppression suffered by the protagonists of the narratives, who figurativize subjects belonging to social classes less favored areas of contemporary Brazilian society. Keywords: Figurativization; Thematization; Interdiscursivity; Veridiction; Luiz Rufatto.